2002
DOI: 10.2170/jjphysiol.52.85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Cold Exposure on Contractile Properties in Slow- and Fast-Twitch Muscles of Rats.

Abstract: Mechanical properties of skeletal muscles or motor performance in mammals [1][2][3][4][5][6][7][8][9], frogs [10,11], and fishes [12][13][14][15] are influenced by changes in environmental temperatures. For example, the maximum velocity of shortening and the maximum rate of tension development decreased at a low temperature in the soleus and extensor digitorum longus (EDL) muscles of rats [4]. Further, Faulkner et al. [1] reported that the maximum and sustained powers in mice EDL muscle were reduced by 40 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 36 publications
(53 reference statements)
4
20
0
Order By: Relevance
“…Similar results were also reported elsewhere [1]. The mean CSA of single muscle fibers expressing pure type I MHC in the soleus of the cold-exposed group was also significantly less than in controls.…”
Section: Japanese Journal Of Physiologysupporting
confidence: 91%
See 4 more Smart Citations
“…Similar results were also reported elsewhere [1]. The mean CSA of single muscle fibers expressing pure type I MHC in the soleus of the cold-exposed group was also significantly less than in controls.…”
Section: Japanese Journal Of Physiologysupporting
confidence: 91%
“…Askew [17] reported that body weight loss was common during chronic exposure to cold environment, because cold exposure elevated energy expenditure almost 2.5 times over the subjects in the warm environment. Such phenomena were also supported by the findings that cold exposure resulted in an increased interscapular brown adipose tissue mass and plasma catecholamine levels in rats [1].…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations